Thermal transfer and moisture resistances of nano-aerogel-embedded foam concrete. (10th March 2020) - Yoon, Hyun-Sub; Lim, Tae-Kyung; Jeong, Sang-Mi; Yang, Keun-Hyeok
Highlights: A new and original aerogel-embedment approach is explored for foam concrete. New foam concrete with better thermal resistance and waterproof is developed. Nano-aerogel embedment is a good way to overcome the limitation of foam concrete. This study plays a leading role in developing nano-aerogel foam concrete. Abstract: The objective of the present study is to develop a new material through the nano-aerogel application for improving the thermal transfer and moisture resistances of preformed foam concrete. Thus, this pioneering study focused on estimating the feasibility of developing high-performance foam concrete with good thermal transfer resistance and waterproof properties by uniformly embedding a highly adiabatic and hydrophobic aerogel with nanosized pores in the porous structure of foam concrete. Methyltrimethoxysilane (MTMS), a silica-based precursor, and tetraethyl orthosilicate (TEOS) were used to manufacture the nano-aerogel material. The nano aerogels were embedded under negative pressure environments of 5–10 torr within the airtight chamber. The test results show that the nano-aerogel-embedded foam concrete possesses a thermal conductivity of approximately 0.08 W/m·K, which corresponds to be 30–50% of that measured for conventional foam concrete. The waterproof capacity of the nano-aerogel-embedded foam concrete was significantly improved, resulting in a water contact angle of 120.8° and exhibiting 75% lower water absorption at an age of 24 hours when compared with the conventional foam concrete. The integrated reactive group of the nano-aerogel materials was uniformly distributed throughout the foam concrete pores. Thus, our results suggest that nano-aerogel-embedded foam concrete has great potential as a source material for insulation in building structures.